Determinan Usia Maternal terhadap Kejadian Hipertensi dalam Kehamilan di Wilayah Kerja Puskesmas Jalaksana Kecamatan Jalaksana Kabupaten Kuningan: Maternal Age Determinants of Hypertensive Disorders in Pregnancy in the Working Area of Jalaksana Primary Health Center - Rosidah, Rosidah; Fitriana, Nana; Meristika Rachman, Sylvia; Rachmawati, Laily; Arieb Shintami, Rica (MPI Press, 2025)
Background: Hypertension is one of the most common complications during pregnancy. This condition not only endangers the mother but may also adversely affect the fetus. In West Java Province, hypertensive disorders of pregnancy remain a significant public health concern. Data from the 2018 Basic Health Research (Riskesdas) reported that the prevalence of hypertension among pregnant women in West Java reached 10.57%, which is higher than the national average of 6.18%. Furthermore, 214 maternal deaths in West Java were attributed to hypertensive complications during pregnancy. Objective: This study aimed to determine the distribution of maternal age among pregnant women with hypertensive disorders of pregnancy in the working area of the Jalaksana Primary Health Center, Jalaksana District, Kuningan Regency. Methods: This study employed a quantitative descriptive design with a cross-sectional approach to describe the maternal age distribution among pregnant women with hypertensive disorders in the working area of the Jalaksana Primary Health Center, Jalaksana District, Kuningan Regency, in 2025. Results: The findings showed that 24 respondents (80%) experienced mild hypertension, while 6 respondents (20%) had moderate hypertension. The respondents were exclusively from two extreme age groups: <20 years (14 women; 46.67%) and >35 years (16 women; 53.33%). Conclusion: These findings reinforce obstetric epidemiological theory that both very young maternal age and advanced maternal age are high-risk factors for hypertensive disorders of pregnancy.